2021
DOI: 10.3390/cancers13153877
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Signature of Circulating MicroRNA Can Predict Osteolytic Bone Disease in Multiple Myeloma

Abstract: Background: Multiple myeloma bone disease (MMBD) constitutes a common and severe complication of multiple myeloma (MM), impacting the quality of life and survival. We evaluated the clinical value of a panel of 19 miRNAs associated with osteoporosis in MMBD. Methods: miRNAs were isolated from the plasma of 62 newly diagnosed MM patients with or without MMBD. First-strand cDNA was synthesized, and relative quantification was performed using qPCR. Lastly, we carried out extensive biostatistical analysis. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Recently, Papanota et al identified let-7b-5p, miR-143-3p, miR-17-5p, miR-214-3p and miR-335-5p as associated with osteolytic bone disease in MM. Both studies are complementary as they use distinct miRNA panels, and contribute to reach the goal of finding novel non-invasive markers for osteolytic lesions [ 41 ]. Interestingly, Kapinas et al showed that miR-29c-3p is highly expressed in fully mature and mineralized mouse-derived osteoblasts [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Papanota et al identified let-7b-5p, miR-143-3p, miR-17-5p, miR-214-3p and miR-335-5p as associated with osteolytic bone disease in MM. Both studies are complementary as they use distinct miRNA panels, and contribute to reach the goal of finding novel non-invasive markers for osteolytic lesions [ 41 ]. Interestingly, Kapinas et al showed that miR-29c-3p is highly expressed in fully mature and mineralized mouse-derived osteoblasts [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…MM ranks second in hematological malignancies, which is considered to be incurable at present (2). About 80%-90% of MM patients will exhibit different degrees of MM-related bone diseases (3). The severity of bone disease increases mortality (4).…”
Section: Introductionmentioning
confidence: 99%
“…Within this prism, scientific research is currently guided towards the investigation of their role in the pathophysiology of malignancy, as well as their putative role as diagnostic and prognostic biomarkers [ 14 ]. The role of miRNAs and other small non-coding RNAs in multiple myeloma and its associated bone disease is a current topic of scientific interest [ 13 , 15 , 16 , 17 ]. In this study, we investigated the role of a group of miRNAs with an established role in human malignancy in MM and proved their association with the clinicopathological characteristics and the disease outcome of MM patients.…”
Section: Discussionmentioning
confidence: 99%